Rancang Bangun Timbangan Beras Digital Dengan Keluaran Tiga Jenis Beras Berbasis Mikrokontroler - Citra Berliana; Mohammad Hafiz Hersyah (Universitas Andalas, 2022)
In today's all-digital era, all aspects of supporting human activities are required to make it easier for humans to support human mobility. One example is the scales that are demanded to be sophisticated to facilitate human work considering how busy the trading process is, especially in traditional markets, one example is rice scales which still use manual scales. So from the problems that occur in traditional markets about scales, the researchers will make digital rice scales.The result of this research is the construction of a digital weighing device with a microcontroller-based weight and price output using a weight sensor or load cell. This tool is equipped with 3 types of rice, namely ordinary rice, white glutinous rice, and black glutinous rice. Then it is also equipped with a feature to change the price of rice in the event of a price change. From the results of tests conducted by researchers, this tool functions well and is able to overcome the problems that have been experienced by traders.